1992
DOI: 10.1007/bf01962535
|View full text |Cite
|
Sign up to set email alerts
|

Comparitive study on protective gloves for handling cytotoxic medicines: a model study with carmustine

Abstract: The quality of protective gloves was studied. Protective gloves are part of the personal safety equipment for staff handling cytotoxic drugs. A study using raster electron microscopic photography, measurement of thickness by micrometer screw and permeability of carmustine by high pressure liquid chromatographic assay was carried out. The results show differences between different types of gloves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 1 publication
1
5
0
Order By: Relevance
“…Data obtained is consistent with that reported in previous studies (1). Data obtained is consistent with that reported in previous studies (1).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Data obtained is consistent with that reported in previous studies (1). Data obtained is consistent with that reported in previous studies (1).…”
Section: Resultssupporting
confidence: 93%
“…International quality standards are stated being more or less insufficient as far as special requirements on protective gloves for handling eytotoxic medicines are concerned [1], With the intention to find data more meaningful several investigators examined protective gloves with regard to the permeability to cytotoxin medicines [2,3,4]. The permeability of three protective gloves for the preparation of eytotoxic medicines available on the market, one protective glove intending to enter the market, and two nol specialised protective gloves which are used together dudng the preparation of cytotoxic medicines was studied.…”
Section: Cytomegalovirusmentioning
confidence: 99%
“…Moreover, the number of chemicals tested varied considerably from one study to the next, ranging from a single chemical to 15 chemicals, but many studies used fewer than 7 chemicals. 9,10,[21][22][23][24][25][26]29 This makes it harder to compare the relative behaviour of different chemicals under identical experimental conditions with the same gloves. In this study we tested 27 chemicals, and only 3 had permeation rates above the US standard ASTM D-6978-05 (carmustine, busulfan and thiotepa) with some gloves.…”
Section: Discussionmentioning
confidence: 99%
“…The chemical most often found to have high permeation rates was carmustine. 8,9,14,15,19,25,[29][30][31] As far as we know, this is the first time that busulfan has been tested in this type of study, and therefore no prior data were available. Finally, thiotepa has already been identified as a compound that permeates gloves in several studies.…”
Section: Discussionmentioning
confidence: 99%
“…Methyl methacrylate used in orthopaedic surgery is the best known chemical against which rubber surgical gloves fail to offer protection (Pegum and Medhurst, 1971;Waegemaekers et al, 1983;Darre et al, 1987;Jensen et al, 1991). It has also been shown that examination gloves do not provide adequate protection against many cytotoxic drugs, and thus surgical gloves have been examined to identify which of these gloves acts as an adequate barrier to these agents Laidlaw et al, 1984;Slevin et al, 1984;Colligan and Horstman, 1990;Dinter-Heidorn and Carstens, 1992;Connor, 1995Connor, , 1999Klein et al, 1999;Singleton and Connor, 1999). A study by Connor and Xiang showed that a 5 min contact with 70% isopropyl alcohol does not increase the permeation of cytotoxic drugs through NR or nitrile rubber material.…”
Section: Introductionmentioning
confidence: 99%